Experimental Studies of the Breakup Dynamics in Turbulent Multiphase Jets - Ng, Chin Hei (My University, 2015)
Breakup of a dispersed phase in a turbulent flow is a classical problem in multiphase flow with many applications in industrial and natural processes. Two different problems have been investigated. The first problem focused on the atomization of a liquid jet. We investigated the effect of the high-speed spray-pattern-shaping air streams on the atomization of a coaxial twin-fluid atomizer. Our experimental data revealed that the pattern air streams contribute to the atomization process, providing the air streams impinge on the liquid jet close to the liquid nozzle (in our atomizer, it is 3.25 liquid nozzle diameter downstream). In comparison with the spray with no pattern air stream, the number density of the larger drops increases at the spray rim of the major axis and decreases at the spray rim of the minor axis. The transport of the larger drops is caused by the pattern air modified flow field. Finally, based on the two-stage instabilities mechanism, we developed a model to predict the drop size of the spray. The second problem is the breakup of particles (air bubbles or oil drops) in a canonical turbulent round jet. Most turbulent breakup models are inspired by the Kolmogorov-Hinze theory, and assume the breakup is the result of the interaction between a particle and an eddy of similar length scale. We have shown that one of these models predicts the breakup of inviscid particles well, but it fails to predict the particle size of viscous particles. High-speed image sequences of the viscous particles breakup event revealed three distinct stages of breakup: deformation, stretching, and disintegration. Quantitative data also sup- ported these observations. The fluctuating behavior of the deformation factor (a particle shape indicator) in the deformation stage suggested that the deformation of a particle is caused by multiple series of eddy collisions. The stretching stage is unique and it is not observed in the breakup of inviscid particles. In this stage, a particle is stretched to multiple times its original size. This suggests the stretching mechanism is caused by the large scale fluid motion, so it contradicts with the Kolmogorov-Hinze theory where the deformation is caused by eddies in the inertial subrange. The disintegration of the stretched ligaments typically results in multiple daughter particles. This is also different from the breakup of inviscid particles, where binary breakup is the norm. A breakup detection and particle tracking algorithm was developed to extract data of particles along their breakup paths. These data were used to develop models for important breakup parameters, such as the breakup probability and the breakup time. We found that the probability of breakup depends on the disruptive effect due to the colliding turbulent eddies, as well as the confinement effects due to the internal viscous stress and the surface restoration pressure. Although the stretching mechanism is due to the large scale turbulent eddy, the stretching/thinning time is dictated by the small scale eddies. This is because as the particle is stretched into a ligament, the ligament is still constantly collided by eddies with length scale similar to the thickness. These eddies are responsible for the thinning of the ligament that ultimately leads to disintegration. The population balance equation describes the evolution of the particle size distribution in the breakup process. One of the closure functions required in this equation is the breakup frequency. The breakup frequency is obtained by combining the breakup time and breakup probability models. The prediction from the breakup frequency model compares favorably with the measured breakup frequency from the experimental data.
Thesis (Ph.D.)--University of Washington, 2015
Keywords: Atomization; Particle breakup; Particle tracking; PIV; Turbulent jet; Viscous particle; Mechanical engineering; mechanical engineering